Influence of Listeria innocua on the growth of Listeria monocytogenes - Carvalheira, Ana (2010)
The growth of Listeria monocytogenes and Listeria innocua strains was monitored during this study: (i) in TSB–YE media and (ii) in a food matrix (pasteurized milk) according to the ISO 11290-1 methodology. Different inocula concentrations and mixtures were tested. The response was shown to be strain dependent. In TSB–YE the inhibition of a L. monocytogenes strain was observed in just one of the three mixtures (L. monocytogenes_1340 with L. innocua_11288) showing a reduction of 1.37 log cfu/ml after 42.5 h and 1.85 log after 66.5 h of incubation. In pasteurized milk the inhibition of L. monocytogenes by L. innocua was always observed when L. innocua was present in higher concentrations than L. monocytogenes. The reverse was also observed but only in one mixture (cocktail of six L. monocytogenes with L. innocua_ 2030c) when the initial concentration of L. monocytogenes was 100 times higher than L. innocua suggesting the phenomenon of quorum sensing. Furthermore, inhibitory activity was not caused by bacteriocins, and no correlation between the growth rate and inhibition was demonstrated.